Increasing participation in colorectal cancer screening: Results from a cluster randomized trial of directly mailed gFOBT kits to previous nonresponders. Issue 6 (23rd September 2014) - Tinmouth, Jill; Patel, Jigisha; Austin, Peter C.; Baxter, Nancy N.; Brouwers, Melissa C.; Earle, Craig; Levitt, Cheryl; Lu, Yan; Mackinnon, Marnie; Paszat, Lawrence; Rabeneck, Linda
<x xml:space="preserve">Abstract</x> Regular screening using guaiac fecal occult blood test (gFOBT) reduces mortality from colorectal cancer (CRC). The objective of this study was to determine whether the addition of a gFOBT kit to a second mailed invitation compared to a second mailed invitation alone increases CRC screening among eligible persons who did not respond to an initial mailed invitation. We conducted a cluster randomized controlled trial, with the physician as the unit of randomization. Participants were persons who had been invited but who had not responded to an invitation for CRC screening in an earlier pilot project. The intervention group received a mailed gFOBT kit and second mailed CRC screening invitation (n = 2, 008) while the control group received a second mailed CRC screening invitation alone (n = 1, 586). The primary outcome was the uptake of gFOBT within 6 months of the second mailing. We found that the uptake of gFOBT was more than twice as high in the intervention group (20.1%) compared to the control group (9.6%). The absolute difference between the two groups was 10.5% (95% CI: 7.5–13.4%, p ≤ 0.0001). In a subsequent adjusted analysis, participants in the intervention group were twice as likely to complete the test as those in the control group (OR = 2.1; 95% CI: 1.6–2.6). These findings suggest that directly mailed gFOBT kits increase CRC screening participation among previous nonresponders to a mailed invitation and that approximately 10 gFOBT kits would have to be sent by mail in order to screen 1 additional person. (ClinicalTrials.gov: NCT01629004).